2019
DOI: 10.1186/s40425-019-0535-y
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination and myocarditis among patients receiving immune checkpoint inhibitors

Abstract: Background Influenza vaccination (FV) is recommended for patients with cancer. Recent data suggested that the administration of the FV was associated with an increase in immune-related adverse events (irAEs) among patients on immune checkpoint inhibitors (ICIs). Myocarditis is an uncommon but serious complication of ICIs and may also result from infection with influenza. There are no data testing the relationship between FV and the development of myocarditis on ICIs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 54 publications
1
40
0
4
Order By: Relevance
“…In the latter subgroup, no negative influence on vaccination outcome was reported. 57 In this context, the study of Awadalla et al 65 should be pointed out. They actually demonstrated that the administration of a influenza vaccination was not correlated with an increased risk of subsequent myocarditis among patients on ICI.…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 95%
See 2 more Smart Citations
“…In the latter subgroup, no negative influence on vaccination outcome was reported. 57 In this context, the study of Awadalla et al 65 should be pointed out. They actually demonstrated that the administration of a influenza vaccination was not correlated with an increased risk of subsequent myocarditis among patients on ICI.…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 95%
“…Indeed, rates of vaccination were lower among patients who did develop ICI-induced myocarditis, and the vaccination was associated with a lower risk of other irAEs, in particular ICI-induced pneumonitis. 65 Unfortunately, there is little data available whether ICI would be beneficial in the management of severe influenza cases.…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, while in a small study, influenza vaccination was associated with a higher rate of irAEs [ 20 ], in an international multicenter registry, the rate of influenza vaccination among ICI-related myocarditis cases was lower than the controls on ICIs who did not develop myocarditis, rejecting any such association of influenza vaccination with development of immune-mediated myocarditis. On the contrary, among those who developed ICI-associated myocarditis, the degree of myocardial injury and the risk of MACE were lower in patients who had received an influenza vaccine [ 21 ].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Seit der ersten berichteten Kardiomyopathie [93,94] zeigten sich verschiedene kardiale Nebenwirkungen wie Myokarditis mit hoher Mortalität [7,95], Perikarditis, Rhythmusstörungen und plötzlicher Herztod [96] [2,103].…”
Section: Seltene Nebenwirkungenunclassified